Interactive “smart” glass as an element of forming an adaptive object-spatial environment - Bryzhachenko, Natalia; Bosyi, Ivan (Art and Design, 2026)
“Smart” glass, as a new material with functional and visual advantages, attracts the attention of architects and designers, opening up new opportunities for modern interiors. The growing number of projects and the lack of generalised experience have determined the relevance of the study. The aim of the work was to analyse trends in the implementation of interactive “smart” glass in the interior design of residential and public buildings, to determine its classification and functional and utilitarian capabilities in terms of forming an adaptive spatial environment. The research was based on a set of general scientific theoretical methods of cognition, which included the implementation of such methods as analysis, synthesis, classification, and generalisation. The author’s definition of the concept of “smart” glass in terms of the formation of an adaptive space was provided. Based on the analysis of practical material, “smart” glass was systematised according to its functional and utilitarian capabilities in the formation of an adaptive object-spatial environment. As a result of the work, methods for implementing various types of “smart” glass in the interior design of residential and public spaces were identified. It was found that the most common are touch and projection technologies, which form a visual and communicative environment in public spaces. In residential interiors, “smart” glass performs a predominantly utilitarian function, contributing to energy conservation and privacy. The results also confirmed the aesthetic and functional potential of “smart” glass as an element of adaptive space. Systematisation of material on the implementation of “smart” glass in modern interiors will enable Ukrainian architects and designers to apply theoretical knowledge in design practice to create interactive object-spatial environments. The presented theoretical developments can serve as a basis for predictive design solutions using certain types of “smart” glass